Bolivar’s portraits: a historiographical state of the art (2012)
This article reflects about the portrait as a genre based ona selection of allegedly live portraits of Simon Bolívar,also, explores the ways in which they have been analyzedhistorically and offers new hypotheses to interpret themfrom the perspective of cultural history. The second partfocuses on a state of the art or critical assessment of thehistoriographical approaches to Bolivar’s iconography,as a starting point for future approaches.